Use of epidurography in the perioperative and acute pain setting. Issue 7 (20th April 2022) - Coleman, John Robert; Hartmann, Patrick; Kona, Matthew; Thiele, Robert A; Salajegheh, Reza; Hanson, Neil A
Abstract : Ensuring proper placement of epidural catheters is critical to improving their reliability for pain control and maintaining confidence in their continued use. This article will seek to address the role of objective confirmation of successful epidural placement via either single view or continuous epidural contrast studies, each creating an 'epidurogram.' Furthermore, the pertinent anatomical corollaries of continuous fluoroscopy used frequently in chronic pain medicine, from which these techniques emerged, will be addressed. Technical radiographic information needed to better understand and troubleshoot these studies is also included. Image examples which highlight the patterns key for successful interpretation of epidurograms will be provided. The aim of this paper was to provide an anesthesiologist unfamiliar with fluoroscopic evaluation of epidural catheters with the tools necessary to successfully conduct and interpret such an examination.